7+7(x)=8+6(x)

Simple and best practice solution for 7+7(x)=8+6(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+7(x)=8+6(x) equation:


7+7(x)=8+6(x)

We simplify the equation to the form, which is simple to understand
7+7(x)=8+6(x)

Reorder the terms in parentheses
7+(+7x)=8+6*(x)

Remove unnecessary parentheses
+7+7x=+8+6+*(+x+)

Reorder the terms in parentheses
7+7x=8+(+6x)

Remove unnecessary parentheses
+7+7x=+8+6x

We move all terms containing x to the left and all other terms to the right.
+7x-6x=+8-7

We simplify left and right side of the equation.
+1x=+1

We divide both sides of the equation by 1 to get x.
x=1

See similar equations:

| a+5*2=9 | | 3m+12=112 | | 11x=6x-15 | | 4x^2-2x=6x^2-2(x^2-x) | | x^4+7x^3+11x^2-7x-12=0 | | 9x+2x-4x=28 | | 19.95+.99m+65.32=144.67 | | 10x+5=2x+45 | | 20q^2-9qr-18r^2= | | 10-4p+35=2-p | | 15p+17q+p-7q-4p= | | -0.04x-x-0.2x=6.2 | | 8-16w=-8(1+2w) | | 8x+2=x-3 | | 4x-9+3x-5+x=7x+2 | | 0.6666667x+6=0.5x+0.25x | | g(h)=-x^2+x-6 | | x^2+y^2-4x-6y+8=0 | | a-3b-2a= | | 25x-30=10x | | x^2+y^2-4x+6y+8=0 | | -10-(-2)= | | 143-2x=43x+18 | | 2.3x-5.4=-10 | | 7(x-3)-4x=-16 | | (x+1)=0 | | (2x+9)=x-3 | | 6x+18y=24 | | 18x+6y=24 | | 8(3n-2)= | | 14-10x=48-24x | | 6x+16-x=7x+4 |

Equations solver categories